Великие философы: Словарь- справочник / Л. В. Блинников - Блинников Леонтий Васильевич (Логос, 1998)
Экземпляры: (20160224) / Инвентарный номер: 34551 / Цена: / Сис.шифр: 87.3 / Авт.знак: Б 69 / ББК: 87.3я2